APPLYING PROJECT BASED LEARNING STRATEGY IN TEACHING SPEAKING AT ENGLISH COMMUNITY COURSE OF AMERICAN CORNER, PATTIMURA UNIVERSITY – AMBON - Salmon J. Hukom (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2017)
As a productive skill, speaking plays important role in expressing and negotiating ideas. This research is aimed to know the improvement of students’ speaking ability towards utilizing Project Based Learning (PBL) Strategy. The Classroom Action Research was used, and it was procedurally consisted of four main steps. The data were collected through observation checklist and oral test. The criterion was set out in order to see the improvement of students’ speaking ability through the application of Project Based Learning Strategy. Thus, the criterion of success in this research was 75% of 25 students (19 students) should at good level (FSI Weighing system). Moreover, 75% of students also should be active involved themselves in teaching-learning process and during doing the project. There were two cycles in this research, and the process of research was stopped in cycle 2 because the students achieved the criteria of success. The results of the research showed that Project Based Learning Strategy has proven improving students’ speaking ability and their involvement in the teaching and learning activities. Moreover, this learning strategy also taught students to become more responsible in doing the project and promoted collaborative work with their colleagues. Besides that PBL strategy could motivate and encourage students to think critically in explaining every single activity they did.